Health needs assessment of rural communities in Asia and Sub-Saharan Africa: a cross-sectional study of selected localities - Muhammad Taufeeq Wahab; Logan Ansell; John Paluyo; Xuxin Lim; Li Jen Lee (Journal of Global Health Economics and Policy)
# Background Rural communities face significant health disparities compared to urban counterparts. Health needs assessments are crucial tools for understanding unmet health needs, but rural communities lack attention and resources for these assessments. This study aims to identify rural health needs in Asia and Sub-Saharan Africa, emphasising the imperative for a universal profile to guide organisations to provide services and improve access to care. # Methods This study adopted a macrosystem perspective – using an epidemiological approach of structured and standardised multiple choice questions on felt needs. Residents were shown 13 products and services and asked to select the options they expressed needs for. Data was collected by trained community health workers via a unified digital platform using convenience sampling. Data was extracted between July 2022 to October 2023 from rural communities in India, Philippines, Indonesia, Cambodia, Kenya, and South Africa. # Results 484 153 responses were collected by consenting residents, 51·8% were female. Majority of respondents were from Indonesia (N=187 802), followed by South Africa (N=113 718), India (N=70 290), Philippines (N=59 657), Kenya (N=49 115), and Cambodia (N=3 661). The need for physician services were the greatest (24·5%), followed by health information through social media (21·1%), and nutrition and wellness products (21·0%). Younger residents (0-20 years) have higher needs for health information via social media, vaccines, and consumer health products. As household income increases, demand for health articles, consumer products, and medications decrease. Those with chronic diseases seek more health articles, physician services, wellness products, though demand for diagnostics and medications is highest in wealthier households. # Conclusions This study highlights the role of community health workers as an efficient and sustainable workforce linking organisations to communities. It identified individual services and health promotion needs as important to rural residents. The findings provide broad priorities for organisations to address unmet needs, stressing the need for further locally contextualised assessments that are needs-based, person-centered, and inclusive of disadvantaged populations.